Different Perspectives on Higher Education: From Germany to the United States - Dean, Shannon; Sevart, Amber (Journal of International Students, 2019)
After visiting four higher education institutions within Germany, reflections on the similarities and differences among the student services counterparts in Europe – both at institutional and federal levels are discussed. Studentenwerk serves as a voluntary association of Germany’s 58 student service organizations, known individually as Studentenwerke. This reflection explores the variety of student services offered in the United States and in Germany through these Studentewerke organizations. Additionally, reflection on the differences in the way higher education is viewed at a societal level is also explored.